Desain Pembelajaran Akhlak dalam Pendidikan Agama Islam di SMPN 1 Kauman Ponorogo - Zukhrufin, Fina Kholij; Anwar, Saiful; Sidiq, Umar (Journal of Islamic Education, 2021)
This study aims to describe and provide understanding to the general public about designs and methods in shaping morals in school children through the subject of Islamic Religious Education. This study uses qualitative methods, namely descriptive research. Data obtained through the processing of data from respondents with observations and interviews, detailed data analysis by coding the data, namely the process of processing data or information material into written segments before interpreting it. The results showed several ways that were used in shaping student morals at SMPN 1 Kauman, including; Teachers participate in religious activities held at schools, teachers participate in making rules and schedule each activity they do, habituation through PAI material which is usually described in class, Habitual prayer dzuhur in congregation, BTQ (read and write Al-Qur'an 'an), Tahfidz (memorizing Al-Qur'an) and Kultum Friday morning. In this way, students of SMPN 1 Kauman were successfully implanted.